Análisis termoeconómico de un proceso de producción de biodiesel que opera de manera convencional y por destilación reactiva (2018)
The thermoeconomic analysis is presented as a criterion of profitability of the process, taking into account the economic value of the exergy losses that exist in the system. To carry out this analysis, it is necessary to determine the exergy losses and the efficiencies of each of the units of the modeled processes. For this part an exergy analysis was carried out applying the load distribution method, which allows to evaluate the overall efficiency of the process. When applying this method in the two production alternatives, it was observed that the production of biodiesel by reactive distillation has an overall efficiency of 36.99%, and that the overall efficiency of the conventional process is 20.87%. Once these efficiencies have been obtained, the next step is to realize the thermoeconomic analysis. For this part, exergy costs and unit costs per exergy unit were determined for each process stream. Finally the thermoeconomic cost of the losses is evaluated and it is observed that for the production of biodiesel by reactive distillation, an exergy saving of $ 254 COP / s is obtained compared with the thermoeconomic value of the losses of the conventional process. Therefore, by implementing a reactive distillation column to the biodiesel process, greater efficiency and profitability are obtained in the process.